1984
DOI: 10.1161/01.hyp.6.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antihypertensive treatment on the behavioral consequences of elevated blood pressure.

Abstract: SUMMARY It was shown in a prior study that mildly hypertensive patients performed significantly less effectively on several sensory-perceptual, cognitive, and psychomotor tests than did matched normotensive controls. To determine whether these deficits are attributable to elevated blood pressure per se, hypertensive and control subjects were recalled for reexamination 15 months after the original tests. Results indicated that those hypertensives in whom blood pressure had been lowered with antihypertensive dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 22 publications
0
34
1
Order By: Relevance
“…Increasing evidences indicate that brain angiotensin II (AII) and some of its fragments, that is AII [3][4][5][6][7][8] (AIV) and AII, [3][4][5][6][7] either ageing directly or by modulation of the activity of other transmitters, are involved in cognitive processes, including learning and memory. 44,45 Although the role of the brain angiotensins in humans remains to be fully explored, experimental studies have demonstrated that intracerebroventricular administration of AII and its fragments facilitated acquisition in active conditioning trials and retention in a passive avoidance situation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing evidences indicate that brain angiotensin II (AII) and some of its fragments, that is AII [3][4][5][6][7][8] (AIV) and AII, [3][4][5][6][7] either ageing directly or by modulation of the activity of other transmitters, are involved in cognitive processes, including learning and memory. 44,45 Although the role of the brain angiotensins in humans remains to be fully explored, experimental studies have demonstrated that intracerebroventricular administration of AII and its fragments facilitated acquisition in active conditioning trials and retention in a passive avoidance situation.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Although the role of the brain angiotensins in humans remains to be fully explored, experimental studies have demonstrated that intracerebroventricular administration of AII and its fragments facilitated acquisition in active conditioning trials and retention in a passive avoidance situation. [46][47][48] The facilitatory effects of angiotensins on memory has been connected mainly with the recently discovered AT4 receptors, which preferentially bind AIV and AII [3][4][5][6][7] and are found in brain areas distinct from those possessing AT1 and AT2 receptors (mainly in the neocortex, hippocampus, dentate gyrus, thalamus and cerebellum). [49][50][51] However, considerable evidence suggests significant, although different, involvement of AT1 and AT2 receptors in cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the early cognitive deficit of young hypertensive individuals can be reversed with an appropriate antihypertensive therapy, as suggested by previous findings. 24,[57][58][59] The association between high BP and anxiety is supported by a large number of case-control studies, which compared either psychological symptoms in hypertensive and control subjects, or BP in patients with a variety of psychiatric disorders and controls. 60 When examining anxiety disorder, Vetere et al 61 found a higher prevalence in hypertensive individuals compared with controls.…”
Section: Discussionmentioning
confidence: 99%